Histopathology of Nephrotoxicity Associated with Administered Water Extract Purple Sweet Potato (Ipomoea batatas) in Mice (Mus musculus) in Stratified Phases of Dose - Meta Maulida Damayanti; Raden Anita Indriyanti; Yuktiana Kharisma; Yuke Andriane; Uci Ari Lantika; Ratna Damailia; Meike Rachmawati (Global Medical & Health Communication (GMHC), 2022)
The main aim of the registered purple sweet potato (Ipomoea batatas) is to provide minimize the adverse chemical drugs, in addition to its anti-inflammatory, antioxidant, and antimicrobial effects. Potentially adverse effects may be observed in laboratory animals in particular, the extent to which this administration can cause toxicity. This study aimed to examine the histopathology of nephrotoxicity associated with administered water extracts of purple sweet potato in mice with stratified doses. The study was conducted at the Biomedical Laboratory, Faculty of Medicine, Universitas Islam Bandung on September 2019. Female mice (Mus musculus) strain Swiss Webster, aged between 6–8 weeks weighing 25 to 30 g, were obtained from Biopharma Laboratory, Bandung. The animal was acclimatized for seven days before being administered water extract purple sweet potato: eleven mice, one control group, and ten treatment groups underwent toxicity doses of purple sweet potato water extract administration. Purple sweet potato variant of Ayamurasaki prepared in various oral doses. The results show in the control group there were no histopathological changes, but in the group administered water extract purple sweet potato from the first phase seems in a mild grade of macrophage accumulation, mild vacuolization of tubular epithelial cells, mild vascular dilatation, and mild hydrophilic degeneration. In the second phase, macrophage accumulation was visible in moderate grades. The LD50 of purple sweet potato extract is greater than 5,000 mg/kgBW. The findings of this study indicate that registration of purple sweet potato extract in confirmatory doses is safe to administer and did not exhibit any mortality. The toxicity test of purple sweet potato water extracts in the kidney exhibits minimal chemical effects.